THE EFFECT OF HUMAN RESOURCE COMPETENCE AND LOCUS OF CONTROL ON THE QUALITY OF VILLAGE FINANCIAL REPORTS IN KABILA BONE DISTRICT, BONEBOLANGO REGENCY, GORONTALO - La Ode Muhamad Amar; Harun Blongkod; Hartati Tuli (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to determine whether human resource competence and locus of control have a significant effect on the quality of village financial reports in Kabila Bone District, Bone Bolango Regency, Gorontalo . This study uses a quantitative method. The data used are primary data obtained from distributing questionnaires. The population of this study were all village officials in Kabila Bone District. Sampling used non-probability sampling. The data analysis method used is Structural Equation Modeling (SEM). The results of this study indicate that human resource competence and locus of control have a significant effect on the quality of village financial reports in Kabila Bone District, Bone Bolango Regency, Gorontalo